Pharmacophore elucidation and molecular docking studies on phosphodiesterase-5 inhibitors - Radwan, Awwad Abdoh (Bioinformation, 2015)
cGMP-binding cGMP-specific PDE, PDE5 plays a key role in the hydrolysis of cyclic guanidine monophosphate. Because cGMP mediates vascular functions, a PDE5 inhibitor that elevates cGMP level is an attractive means for vasodilatation and treatment of erectile dysfunction. In this paper we report the elucidation of the common pharmacophore hypothesis of different classes of PDE5 inhibitors. Using LigandScout program, pharmacophore modelling studies were performed on prior reported potent PDE5 inhibitors with a variety of scaffolds in order to identify one common set of critical chemical features of these PDE5 inhibitors 1-52. The best pharmacophore model, model-1, characterized by four chemical features: one aromatic ring, one hydrophobe, one hydrogen acceptors and one hydrogen donor. Using Dock6 program, docking studies were performed in order to investigate the mode of binding of these compounds. The molecular docking study allowed confirming the preferential binding mode of different classes of PDE5 inhibitors inside the active site. The obtained binding mode was as same as that of vardenafil, X-ray ligand with different orientation with varied PDE5 inhibitors׳ scaffold.